Prevention of mother-to-child transmission of HIV: challenges for the current decade - Newell Marie-Louise (The World Health Organization, 2001)
In June 2001 the United Nations Special Assembly on HIV/AIDS set reduction targets of 20% and 50% for the numbers of children newly infected with HIV by 2005 and 2010 respectively. Are these targets achievable? Antiretroviral monotherapy during pregnancy, delivery, and the neonatal period can reduce the rate of mother-to-child transmission of HIV-1 by two-thirds in non-breastfeeding populations. Shorter and simpler regimens of monotherapy have been associated with a reduction of 50% in such transmission among non-breastfeeding populations and of up to 40% in breastfeeding populations. Delivery by elective caesarean section is associated with a halving of the risk of mother-to-child transmission. However, breastfeeding poses a substantial additional risk of acquisition of HIV, and if prolonged it more than doubles the overall rate of transmission. Rates below 2% are being reported from settings where combination therapy is applied during pregnancy and delivery, delivery is by elective caesarean section, and breastfeeding does not take place. In breastfeeding populations where elective caesarean delivery is not an option but peripartum antiretroviral therapy is used, rates at six weeks are about 10% but can be 25% or more after 18 months of breastfeeding. More widely applicable interventions are being developed, such as cleansing of the birth canal and antiretroviral therapy during the breastfeeding period.